Poéticas expressivas em redes midiáticas: análise e projeto experimental - Bona, Carla Marangoni De (2012)
This research aims to investigate expressive practices in projects that make use of content generated by user (s), reflecting on the nature of digital media communication and expressive aspects. Aims also contribute to the reflection on the creative processes in digital networks, their limitations and possibilities. The creative processes that permeate media networks are characterized by multiplying forms of publishing, sharing and organizing information. Moreover, there is a diversity of spaces for interaction among the users leveraging the collective work processes, affective exchange, production and circulation of information. In short, the social construction of knowledge supported by information technology (PRIMO, 2007). Methodologically, is composed of three stages: a literature review, analysis and experimentation: development of a poetic work. The theory is based on references on the Internet and the network society (Manuel Castells, Kazys Varnelis and André Lemos), intimacy/exposure on the network (Paula Sibilia, Guy Debord and André Lemos), collaboration (Karla Schuch Brunet, James and Thelma Surowieki Johnson), authorship (Michel Foucault, Stuart Hall, Cecilia A. Salles), creative processes in networks (Almeida Salles Cecilia and Lucy Lion), aesthetics of database and data visualization (Cristine Paul, Victoria Vesna and Lev Manovich). The corpus of analysis consists of projects designed to media networks that put on the agenda the above mentioned concepts and contribute to the understanding of collaborative poetry in contemporary society. They are: We Feel Fine, Post Secret, and youTAG Tele_bits 2.0. The poetic experimentation, coloroflove.us the project, discusses the procedures that make possible the maintenance of interests on the project and analyzes viral propagation in such networks. Developed in PHP with MySQL database, the coloroflove.us is online since 29/09/10